Figure of the dikpala Agni - Temples of India Project Team (Jio Institute, 2024)
A figure of the dikpala Agni is positioned at one of the karna (corner projection) of the Harshnath Temple. It is on the karna of the southeastern corner, accompanied by his vahana, a ram. On either side of him, surasundaris occupy places at the pratirathas and salilantara-recesses.